Perencanaan Enterprise Architecture Sistem Informasi pada Dinas Komunikasi dan Informatika Menggunakan Framework TOGAF ADM - Riska Angraini; Mauli Fathia Zahra; Najwa Alifah Zulfikar; Irzi Ahmad Fahrozi; Ibrahim Syahputra; Rizky Alpiansyah; Raihan Aulia Nugraha; Ika Yusnita Sari (CV. ITTC INDONESIA, 2026)
The use of information systems in government agencies requires structured architectural planning to align with organizational goals. The Medan City Communication and Information Agency (Diskominfo) still faces problems such as unintegrated information systems, scattered data management, and several administrative processes that are still carried out manually. Therefore, enterprise architecture planning is needed as the basis for targeted information system development. This study aims to develop an enterprise architecture plan for the information system at Diskominfo Medan City using the TOGAF framework with the Architecture Development Method (ADM). The research uses a case study approach through observation, interviews, and documentation studies with the application of TOGAF ADM in Phases A to D. The data used in this study includes business process data, existing information system data, and policy and procedure documents obtained from the Medan City Communication and Information Agency. The results of this study are an information system architecture design that describes the existing conditions (As-Is), proposed conditions (ToBe), and gap analysis as recommendations for information system development within the Medan City Communication and Information Agency.